Dual RNA Sequencing Analysis of Bacillus amyloliquefaciens and Sclerotinia sclerotiorum During Infection of Soybean Seedlings by S. sclerotiorum Unveils Antagonistic Interactions - Cheng, Yunqing; Gao, Xin; He, Hongli; Zhang, Xingzheng; Wang, Ran; Liu, Jianfeng (Frontiers in Microbiology, 2022)
Soybean Sclerotinia stem rot is caused by S. sclerotiorum infection, which causes extensive and severe damage to soybean production. Here, we isolated and patented a Bacillus amyloliquefaciens strain, and used it to verify the antagonistic effect of B. amyloliquefaciens on S. sclerotiorum and to explore the possible underlying mechanism. First, we conducted a plate confrontation experiment using the two microbes. Then, inoculation of soybean (Glycine max) seedlings with S. sclerotiorum (Gm-Ss), B. amyloliquefaciens (Gm-Ba), and their combination (Gm-Ba-Ss) was performed, followed by dual RNA sequencing analysis. Plate confrontation and inoculation experiments showed that B. amyloliquefaciens significantly antagonized S. sclerotiorum growth. The average number of fragments per kilobase of transcript per million fragments mapped of S. sclerotiorum transcripts in Gm-Ss and Gm-Ba-Ss inoculation treatments were 117.82 and 50.79 respectively, indicating that B. amyloliquefaciens strongly inhibited gene expression of S. sclerotiorum. In contrast, the average number of fragments per kilobase of transcript per million fragments mapped of B. amyloliquefaciens transcripts in Gm-Ba and Gm-Ba-Ss inoculation treatments were 479.56 and 579.66 respectively, indicating that S. sclerotiorum promoted overall gene expression in B. amyloliquefaciens. For S. sclerotiorum, 507 upregulated and 4950 downregulated genes were identified among 8975 genes in the paired comparison Gm-Ba-Ss vs Gm-Ss. These differentially expressed genes (DEGs) were significantly enriched in the ribosome (ko03010) KEGG pathway. Additionally, for B. amyloliquefaciens, 294 upregulated and 178 downregulated genes were identified among all 3154 genes in the paired comparison Gm-Ba-Ss vs Gm-Ba, and these DEGs were mainly and significantly enriched in metabolism-related KEGG pathways, including the citrate cycle (ko00020) and carbon metabolism (ko01200). We concluded that B. amyloliquefaciens inhibits the expression of genes encoding the ribosomal subunit of S. sclerotiorum, resulting in protein synthesis inhibition in S. sclerotiorum, and thus had a strong antagonistic effect on the fungus. This study provides a scientific basis for the biological control of S. sclerotiorum by B. amyloliquefaciens.